Sanjaya Lall: Industrial Competitiveness and Technological Capabilities - Osorio-Barreto, Daniel; Cardona-Arenas, Carlos David; Naranjo-Herrera, Cristhian Guillermo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper seeks to identify the theoretical and empirical development of the research field of industrial competitiveness on the concept of technological capabilities proposed by Sanjaya Lall in the framework of firms. A methodology consisting of the systematic review of literature during the period between 1987 and 2019 is proposed. As the main finding, the study clearly identified three future research lines on technological capabilities dynamics, structure incentives and the analysis of macro-fundamental variables, which allows to conclude that there is an emerging field of study in relation to the interactions between technological capabilities, from its economic perspective, and resources and capabilities from the strategic and administrative literature. So, this study contributes significantly to the theoretical reflection on the relationship between technological capabilities and management, the metrics of the firm's resources, and the scenarios, environments and learning processes at firm´s individual, collective, organizational and interorganizational level.